(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2025)
The purpose of this study is to develop new properties of product fuzzy graphs in the form of tensor product operations. The research method used consists of a preliminary stage, a stage of defining and theorems, a stage of proving theorems and verifying research results. The results of this study obtained the definition of tensor product operations from fuzzy graph products. Furthermore, it was found that the graph resulting from tensor product operations is a fuzzy graph, the tensor product operations of strong product fuzzy graphs are strong, and the tensor product operations of complete product fuzzy graphs are strong.